Ouija board: A transcription factor evolved for only one target in steroid hormone biosynthesis in the fruit fly Drosophila melanogaster. Issue 5 (19th October 2016) - Niwa, Yuko S.; Niwa, Ryusuke
ABSTRACT: Transcription factors generally regulate gene expression of multiple targets. In contrast, our recent finding suggests that the zinc finger protein Ouija board controls steroid hormone biosynthesis through specific regulation of only one gene spookier in Drosophila . It sheds light on a specialized but essential factor that evolved for one target.